Eine arabisch-äthiopische Wort- und Satzliste aus Jerusalem vom 15. Jahrhundert - Franz-Christoph Muth (Afriques)
In the first half of the fifteenth century in Jerusalem, an unknown amateur lexicographer wrote a "Travel Guide". He collects lists of useful vocabulary and common phrases in spoken Arabic and "primitive Ethiopian" with an intuitive transliteration in Latin characters, and he translates them in Italian and Latin. In the late Middle Ages, this genre will flourish for the pilgrims visiting the Holy Land. The article presents these documents in their original version and then ordering as such: elements and natural phenomena; plants, fruits and vegetables, food; animals; clothing; weapons, tools, architecture and colours; useful sentences. Then the author studied the methods used by the compiler: Arabic was certainly the source language as evidenced by many Arabic words given as would-be Ethiopian terms.